2016
DOI: 10.1016/j.cub.2016.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Antagonistic Male Signals Manipulate Germline and Soma of C. elegans Hermaphrodites

Abstract: Males and females pursue different reproductive strategies, which often bring them into conflict-many traits exist that benefit one sex at a cost to another [1]. Decreased female survival following mating dramatically demonstrates one aspect of this phenomenon [2-5]. Particularly intriguing is the evidence that secreted compounds can shorten lifespan of members of the opposite sex in Drosophila [6] and Caenorhabditid nematodes [7] even without copulation taking place. The purpose of such signals is not clear, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
106
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(112 citation statements)
references
References 38 publications
6
106
0
Order By: Relevance
“…Laboratory evolution experiments additionally showed that male–male competition can lead to strong sexual selection and cause changes in the competitiveness of male sperm (Figure 14) (LaMunyon and Ward 2002; Anderson et al 2010; Palopoli et al 2015). Interactions of hermaphrodites with males can lead to reduced life span and offspring production of hermaphrodites (Gems and Riddle 1996; Wegewitz et al 2008; Shi and Murphy 2014; Palopoli et al 2015), apparently through mechanical damage of the cuticle (Woodruff et al 2014) or via secreted harmful compounds (Maures et al 2014) that can decrease the number of germline progenitor cells, fat storage, or somatic stress resistance (Shi and Murphy 2014; Aprison and Ruvinsky 2016). These costs of mating or contact with males are possibly a consequence of sexual selection, which can favor the production of manipulative and damaging substances by males to increase male reproductive rate (Arnqvist and Rowe 2005).…”
Section: Intraspecific Interactionsmentioning
confidence: 99%
“…Laboratory evolution experiments additionally showed that male–male competition can lead to strong sexual selection and cause changes in the competitiveness of male sperm (Figure 14) (LaMunyon and Ward 2002; Anderson et al 2010; Palopoli et al 2015). Interactions of hermaphrodites with males can lead to reduced life span and offspring production of hermaphrodites (Gems and Riddle 1996; Wegewitz et al 2008; Shi and Murphy 2014; Palopoli et al 2015), apparently through mechanical damage of the cuticle (Woodruff et al 2014) or via secreted harmful compounds (Maures et al 2014) that can decrease the number of germline progenitor cells, fat storage, or somatic stress resistance (Shi and Murphy 2014; Aprison and Ruvinsky 2016). These costs of mating or contact with males are possibly a consequence of sexual selection, which can favor the production of manipulative and damaging substances by males to increase male reproductive rate (Arnqvist and Rowe 2005).…”
Section: Intraspecific Interactionsmentioning
confidence: 99%
“…Caenorhabditis females secrete pheromones that attract males (Chasnov et al, 2007), while C. elegans hermaphrodites modify their pheromone profile according to their sperm status, becoming more attractive to males once they have used up their own sperm (Garcia et al, 2007; Kleemann and Basolo, 2007; Morsci et al, 2011). Male ascaroside pheromones can directly affect the reproductive system of hermaphrodites, aiding recovery from heat stress and delaying the loss of hermaphrodite germline stem cells (Aprison and Ruvinsky, 2015, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…1,2 These compounds are derived from glycosides of the dideoxy sugars l -ascarylose and l -paratose, which are decorated with diverse building blocks from amino acid, nucleoside, carbohydrate, and fatty acid metabolism (Figure 1). 1,3 NDMMs function as signaling molecules that regulate many aspects of nematode life history, including development, 47 lifespan, 8,9 morphology, 10 social communication, 6,7,1115 as well as interactions with other species. 1618 Since even small changes in the chemical structures of NDMMs can greatly affect biological activity and NDMMs can be active at extremely low (femtomolar) concentrations, 12,19 requirements for the purity of synthetic samples for bioassays are particularly stringent.…”
mentioning
confidence: 99%